The effect of molecular structure, band gap energy and morphology on the dc electrical conductivity of polyaniline/aluminium oxide composites. (November 2015) - Kanwal, F.; Batool, A.; Adnan, M.; Naseem, S.
Abstract : Conducting composites of polyaniline have successfully synthesised with different weight percentages of aluminium oxide (0–40%) dispersed during polymerisation of polyaniline. These composites were characterised by X-ray diffraction analysis, UV–visible absorption spectroscopy, scanning electron microscopy and standard two probe method to study the influence of doping on their structure, effect of band gap energy and surface morphology on conductivity of polyaniline. It was perceived that dispersion of aluminium oxide in polyaniline matrix has introduced good structural and conducting properties. The percolation threshold for conductivity was observed at 10 wt-% of metal oxide content in polyaniline matrix owing to semicrystalline behaviour, small band gap energy, homogeneous dispersion and reduction in grain boundary volume as inferred from X-ray diffraction, ultraviolet and scanning electron microscopy studies.